Assessment of Antibiotic Use in ICU Patients with Pneumonia Using ATC/DDD as a Quantitative Analysis Method - Mareta Rindang Andarsari; Zedny Norachuriya; Sarah Mahmudatun Nabila; Toetik Aryani; Alfian Nur Rosyid (Universitas Airlangga, 2022)
Background: Pneumonia is an infection of the lung tissue which is mainly caused by bacteria. High utilization and inappropriate use of antibiotics increase resistant bacteria, morbidity, mortality, and treatment cost. Quantitative evaluation becomes one of the indicators to assess the use of antibiotics which is one indicator of the quality of the antimicrobial resistance control program. Objective: This study aimed to evaluate the use of antibiotics an effort to increase the rationality of the use of antibiotics. Methods: This study was a retrospective observational study with a sampling method of time-limited sampling in Universitas Airlangga hospital from January until December 2019. Quantitatively using Anatomical Therapeutic Chemical (ATC)/Defined Daily Dose (DDD). Result: The samples obtained were 68 severe pneumonia patients who met the inclusion criteria. From the result of the study, there were 13 types of antibiotics used for pneumonia therapy, and the three most used were Levofloxacin, Ceftriaxone, and Meropenem, with a total of all antibiotics 73.64 DDD/100 patients-days. Most useful is parenteral Levofloxacin at 21.92 DDD/100 patient-days, Ceftriaxone at 20.45 DDD/100 patient-days and Meropenem at 14.29 DDD/100 patient-days. Conclusion: The DDD value indicates high antibiotic usage, but high antibiotic use does not imply unreasonable drug use, so we must undertake a qualitative review of antibiotic use.